Pengaruh Besar Besar Butiran Agregat Kasar terhadap Kuat Tekan Beton Normal: Penelitian - Shidik Permana; Afrie Nardiansyah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to determine the effect of variations in coarse aggregate sizes on the compressive strength of normal concrete with a target strength of f’c 20 MPa. Three types of coarse aggregates were used in the concrete mix: 10–20 mm, 20–30 mm, and a combination of both. The research was conducted at PT. Karya Adi Kencana Laboratory using a quantitative experimental method. Cylindrical specimens were tested at the age of 7, 14, and 28 days to measure compressive strength. The results showed that all aggregate variations achieved compressive strength exceeding 100% of the planned strength (20 MPa) at 28 days. The 10–20 mm aggregate produced the highest strength at 109.3%, followed by 20–30 mm at 107.65%, and the combined aggregate at 106.15%. These findings indicate that smaller aggregate sizes provide better compaction and interparticle bonding, leading to higher concrete strength. The results are consistent with previous studies by Hujiyanto et al. (2024), Hermawati (2023), and Ifantri Sugiono (2023), which state that the maximum size of coarse aggregate significantly affects concrete strength. Utilizing 10–20 mm local aggregates is proven to be an effective and economical option for producing high-quality concrete.